The Roberts Court and Criminal Justice: An Empirical Assessment - Smith, Christopher E. (American journal of criminal justice, 2015)
An empirical examination of decisions by the Roberts Court can illuminate the contemporary Supreme Court’s impact on criminal justice. The Court’s decisions and the voting patterns of its justices confirm the Roberts Court’s generally conservative reputation with respect to criminal justice. However, contrary to commentators’ assertions about a five-member conservative majority actively reshaping criminal justice law in a rights-restricting fashion, the deeply-divided Court actually produces a notable number of rights-protective liberal decisions. Indeed, when the Roberts Court is most deeply divided on criminal justice issues, it has produced more liberal decisions than conservative decisions, due largely to the voting patterns of Justice Anthony Kennedy whose moderate voting record places him at the Court’s center. Justices Antonin Scalia and Clarence Thomas have also made important contributions to liberal decisions in divided cases. Generalizations about the Roberts Court’s conservatism and judicial activism in criminal justice are overstated without recognition of the voting patterns that have contributed to the production of rights-maintaining and rights-expanding liberal decisions.